2020
DOI: 10.1080/08897077.2019.1695038
|View full text |Cite
|
Sign up to set email alerts
|

Persisting Gaps in M-OUD Coverage at Post-Discharge Recovery Houses Necessitate our Continued Advocacy

Abstract: Effective treatment of opioid use disorder (OUD) must target both the medical and psychosocial aspects of a patient's condition. This, in turn, requires a collaboration between medical providers and social supports. We would like to illustrate a key difficulty in this collaboration for some patients in our country: many post-discharge recovery houses continue to refuse to allow patients to remain on medication treatment for OUD (M-OUD). This barrier to M-OUD access in recovery houses is a significant obstacle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“… Nyamathi et al (2004) Los Angeles, CA Cohort study Women experiencing homelessness Recent substance use treatment was not significantly associated with a motivation to quit for people who used heroin. Patel et al (2020) Nashville, TN Descriptive report Discharged patients with SUDs Of the recovery houses that accepted discharged patients from Vanderbilt Medical Center in 2018, 12.5 % allowed patients to remain on buprenorphine/naloxone, 0 % allowed patients to remain on MMT, and 19 % completely allowed naltrexone maintenance therapy. Reynoso-Vallejo et al (2008) Massachusetts, USA Cohort study Latino men who inject drugs Homelessness was associated with a decreased likelihood of entering methadone maintenance (OR = 0.41, 95 % CI 0.36, 0.47).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Nyamathi et al (2004) Los Angeles, CA Cohort study Women experiencing homelessness Recent substance use treatment was not significantly associated with a motivation to quit for people who used heroin. Patel et al (2020) Nashville, TN Descriptive report Discharged patients with SUDs Of the recovery houses that accepted discharged patients from Vanderbilt Medical Center in 2018, 12.5 % allowed patients to remain on buprenorphine/naloxone, 0 % allowed patients to remain on MMT, and 19 % completely allowed naltrexone maintenance therapy. Reynoso-Vallejo et al (2008) Massachusetts, USA Cohort study Latino men who inject drugs Homelessness was associated with a decreased likelihood of entering methadone maintenance (OR = 0.41, 95 % CI 0.36, 0.47).…”
Section: Resultsmentioning
confidence: 99%
“…Of the sixty included studies, twenty-seven reported on opioid use treatment access and engagement among PEH ( Amodeo et al, 2004 ; Bachhuber et al, 2015 ; Bauer et al, 2016 ; Corsi et al, 2007 ; Daniulaityte et al, 2019 ; Deck and Carlson, 2004 ; Dunn et al, 2019 ; Englander et al, 2020 ; Eyrich-Garg et al, 2008 ; Hoffman et al, 2019 ; Kelly et al, 2018 ; Krawczyk et al, 2020 ; Krull et al, 2011 ; Lundgren et al, 2003 ; Masson et al, 2002 ; Midboe et al, 2019 ; Nyamathi et al, 2004 ; Patel et al, 2020 ; Reynoso-Vallejo et al, 2008 ; Rivers et al, 2006 ; Robbins et al, 2010 ; Royse et al, 2000 ; Shah et al, 2000 ; Simon et al, 2017 ; Timko et al, 2016 ; Upshur et al, 2018 ; Van Ness et al, 2004 ). While most were conducted among general populations of people who use opioids, five evaluated characteristics of treatment engagement exclusively among homeless-experienced populations ( Bauer et al, 2016 ; Midboe et al, 2019 ; Nyamathi et al, 2004 ; Robbins et al, 2010 ; Upshur et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations